The fate of the 20th Century Heritage. Research and Actions - Giovanna Franco; Stefano Francesco Musso (Anuari d’Arquitectura i Societat)
20th Century Architecture is an Heritage at risk, mostly caused by abandonment, degradation, underestimation. Nevertheless, the increase of interest and expansion of Heritage leads us to question the values that even the most recent architecture acquires, and therefore, its eventual need of protection. There is a need of a process of understanding and of selection, based on criteria shared by the largest community. This was the main goal of national and international reserches here presented concerning the architectural production of the 20th Century. The observation of single constructions and urban complexes, that are very close to us in time, leads to reflect on their meanings and values highlighting the essential problem of placing them in history. The more the heritage is the result of recent episodes, the more we perceive it as inserted in a processing dimension, of simultaneity of events and actions – almost like the news - which tend to legitimize any form of change, in a perspective linked to its contemporary condition. Research has let the richness of this inheritance emerge, in significance and value, focusing the attention from the simple materiality of the buildings to the possible modes and forms of their more total and mature interpretation.